2018
DOI: 10.1159/000486454
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment and Chemotherapy of Adult Primary Liver Sarcoma: Experiences from a Single Hospital in China

Abstract: Background: The aim of this study is to improve the preoperative diagnostic accuracy and treatment results by investigating the clinical features and prognosis of primary liver sarcoma (PLS). Methods: Clinical data, surgical treatments, adjuvant chemotherapy, and prognosis of 17 PLS patients whose diseases were pathologically confirmed were retrospectively analyzed. Results: The main clinical symptoms included epigastric pain in 9 patients, epigastric distention in 7, and loss of appetite in 4; these symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…In the venous phase, the degree of enhancement started to drop signi cantly, with uneven enhancement or brim enhancement and no central necrosis. This contradicts a recent summary of a retrospective study of 14 patients with HSC, which found that CECT revealed progressive or persistent heterogeneous enhancement, as well as central necrosis [30] . This could be due to the small number of patients in our HSC group who underwent CECT.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In the venous phase, the degree of enhancement started to drop signi cantly, with uneven enhancement or brim enhancement and no central necrosis. This contradicts a recent summary of a retrospective study of 14 patients with HSC, which found that CECT revealed progressive or persistent heterogeneous enhancement, as well as central necrosis [30] . This could be due to the small number of patients in our HSC group who underwent CECT.…”
Section: Discussioncontrasting
confidence: 66%
“…They are unusual, featured with nonspeci c symptoms, and often present asymptomatic until they have become large, leading to a clinical dilemma. Clinically, asymptomatic, epigastric pain, bloating, anorexia, fatigue and weight loss are main symptoms of these two liver tumors [11][12][13][14] . It has been reported that HSC and HS are initially misdiagnosed as hepatic abscess, HCC, and malignant tumor (MT) by imaging [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…The poor prognosis of GC is mainly decided by local and systemic metastasis . Surgery is the most effective treatment for resectable gastric cancer . Despite the recent therapeutic advances, the overall long‐term outcomes of GC remain poor.…”
Section: Introductionmentioning
confidence: 99%
“…2 Surgery is the most effective treatment for resectable gastric cancer. 2,3 Despite the recent therapeutic advances, the overall long-term outcomes of GC remain poor. The TNM staging system, which is developed by American Joint Committee on Cancer (AJCC), provides a useful benchmark for prognostic prediction and establishment of treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, many patients have unresectable disease or are not surgical candidates due to poor performance status or comorbidities. For these patients, systemic chemotherapy is employed treatment although response rates are low [ 15 , 16 , 17 ]. Thus, localized transcatheter liver-directed therapies (LDTs), including trans-arterial chemoembolization (TACE), bland embolization (TABE), and Yttrium-90 (Y90) radioembolization (TARE), offer a valuable treatment alternative for these patients.…”
Section: Introductionmentioning
confidence: 99%